2012
DOI: 10.1177/1352458512448108
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and alcohol intakes have no association with risk of multiple sclerosis

Abstract: Background The association between alcohol and caffeine intakes and risk of multiple sclerosis (MS) is unclear; no prospective studies have examined this relationship. Objective We examined intakes of alcohol and caffeine in relation to risk of multiple sclerosis. Design Intakes of alcohol and caffeine were examined in relation to risk of MS in two large cohorts of women, the Nurses’ Health Study (NHS; 92,275 women followed from 1980 to 2004) and Nurses’ Health Study II (NHS II; 95,051 women followed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 25 publications
5
51
4
Order By: Relevance
“…Chen and Chern (2011) reviewed the current evidence for the effects of methylxanthines and adenosine receptors in general, including the effects of caffeine (a xanthine) and concluded that caffeine indeed appears to have applicable neuroprotective properties especially with respect to the most common neurodegenerative disorders including MS 25 . This is supported by a study in Europe by D'hooghe et al (2011) who also concluded that coffee was inversely associated with the progression of relapsing (discrete attacks) MS but not in progressive MS 86 . Still, there is some conflicting evidence concerning caffeine intake and MS. A study by Massa et al (2013) did not support an association with caffeine intake and MS 87 , yet little research directly concerned chlorogenic acid and MS has been performed.…”
Section: Coffee and Multiple Sclerosissupporting
confidence: 71%
See 1 more Smart Citation
“…Chen and Chern (2011) reviewed the current evidence for the effects of methylxanthines and adenosine receptors in general, including the effects of caffeine (a xanthine) and concluded that caffeine indeed appears to have applicable neuroprotective properties especially with respect to the most common neurodegenerative disorders including MS 25 . This is supported by a study in Europe by D'hooghe et al (2011) who also concluded that coffee was inversely associated with the progression of relapsing (discrete attacks) MS but not in progressive MS 86 . Still, there is some conflicting evidence concerning caffeine intake and MS. A study by Massa et al (2013) did not support an association with caffeine intake and MS 87 , yet little research directly concerned chlorogenic acid and MS has been performed.…”
Section: Coffee and Multiple Sclerosissupporting
confidence: 71%
“…This is supported by a study in Europe by D'hooghe et al (2011) who also concluded that coffee was inversely associated with the progression of relapsing (discrete attacks) MS but not in progressive MS 86 . Still, there is some conflicting evidence concerning caffeine intake and MS. A study by Massa et al (2013) did not support an association with caffeine intake and MS 87 , yet little research directly concerned chlorogenic acid and MS has been performed. MCI=mild cognitive impairment; Ns= not significant; SBP=systolic blood pressure.…”
Section: Coffee and Multiple Sclerosissupporting
confidence: 71%
“…71 However, in two large cohorts of women participating in the Nurse Health Study, the association between MS risk and alcohol or caffeine intake was not confirmed. 72 Therefore, due to limited research and inconsistent findings, caution is needed in interpreting these results and their significance warrants further investigation.…”
Section: Alcohol and Caffeinementioning
confidence: 99%
“…On the other hand, another study showed that the duration of alcohol consumption by patients with MS was correlated with disability and lesion load in magnetic resonance imaging examinations [13]. A very large epidemiological database showed that alcohol consumption was not a risk factor for the development of MS [14,19,20].…”
Section: Resultsmentioning
confidence: 99%
“…From reading titles and abstracts, 312 papers did not fulfil the specified criteria and, therefore, 30 papers were initially selected for full consideration. In the end, eleven research articles published between 2004 and 2016 were included in this review [8][9][10][11][12][13][14][15][16][17][18]. Papers discussing the role of lifestyle habits in relation to MS were typically very recent publications.…”
Section: Resultsmentioning
confidence: 99%